Fluorescent–Electrochemical–Colorimetric Triple-Model Immunoassays with Multifunctional Metal–Organic Frameworks for Signal Amplification - Ning Xia; Chuye Zheng; Gang Liu (Biosensors, 2025)
Multimode immunoassays based on multiple response mechanisms have received great attention due to their capacity to effectively improve the accuracy and reliability of biosensing platforms. However, few strategies have been reported for triple-mode immunoassays due to the shortage of multifunctional sensing materials and the incompatibility of signal transduction methods in different detection modes. In this work, a fluorescent–electrochemical–colorimetric triple-mode immunoassay platform was proposed with Cu-based metal–organic frameworks (MOFs) as the signal labels. The captured Cu-MOFs were successfully decomposed under an acidic condition, leading to the release of numerous Cu2+ ions and 2-aminobenzene-1,4-dicarboxylic acid (NH2-BDC) ligands. The released NH2-BDC were determined by fluorescence titration. Meanwhile, the released Cu2+ were readily quantified by differential pulse voltammetry (DPV) and simply detected through the catalytic oxidation of chromogenic substrate 3,3′,5,5′-tetramethylbenzidine (TMB). Taking alpha-fetoprotein (AFP) as a model analyte, the designed triple-mode immunoassays showed good performances with the linear range of 10–200 pg/mL, 10–200 pg/mL, and 1–100 pg/mL for the fluorescent, electrochemical, and colorimetric modes, respectively. The proposed triple-mode biosensing platforms show great potential for the applications in disease diagnosis, since they can be easily extended to other bioassays by changing the targets and recognition elements.